2020
DOI: 10.1177/1756284820945388
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a mailed fecal immunochemical test outreach: a Medicare Advantage pilot study

Abstract: Background: Mailed fecal immunochemical test (FIT) outreach effectively increases colorectal cancer (CRC) screening but is underutilized. This pilot aimed to determine the use of FIT for CRC screening among Medicare Advantage enrollees when offered via mailed outreach and the factors associated with FIT return. Methods: Our pilot study included Medicare Advantage enrollees who were 50–75-years old, not up to date with CRC screening, and had a billable primary care encounter in the prior 3 years. Eligible patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
1
14
1
Order By: Relevance
“…Despite this difference in settings, the adherence rates for FIT and FOBT used in the base case scenario are conservative when compared with other reported adherence rates in other non-Medicare populations, ranging from 14%-29% [38,41,44]. Few data also exist on reported real world adherence data for follow-up colonoscopies [41,45].…”
Section: Accepted Manuscript Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Despite this difference in settings, the adherence rates for FIT and FOBT used in the base case scenario are conservative when compared with other reported adherence rates in other non-Medicare populations, ranging from 14%-29% [38,41,44]. Few data also exist on reported real world adherence data for follow-up colonoscopies [41,45].…”
Section: Accepted Manuscript Discussionmentioning
confidence: 97%
“…This is consistent with a previous study that found that when mt-sDNA was offered to Medicare patients previously nonadherent with CRC screening, 88% completed mt-sDNA tests within 12 months and, of those with a positive mt-sDNA test, 96% went on to complete a follow-up colonoscopy [39]. Though mt-sDNA is currently the only stool-based strategy with fully integrated patient navigation, other studies, including a systematic review, have noted that the use of patient navigation and patient reminders are associated with increased adherence to CRC screening across various modalities, including FIT [37,40,41]. Other differences in the practical aspects of stool-based screening strategies may also contribute to test-specific variations in adherence to follow-up colonoscopies.…”
Section: Accepted Manuscript Discussionmentioning
confidence: 99%
“…Interestingly, previous studies evaluating the effect of outreach programs related to stool-based tests mostly included the Medicare population. 5 , 16 , 17 Our study adds to the existing research literature showing the impact of inreach and outreach interventions for the mt-sDNA CRC screening test among a younger commercially insured employer population.…”
Section: Discussionmentioning
confidence: 88%
“…Other adherence rates for the stool-tests have been published that vary by the population evaluated and how adherence was defined. [19][20][21][22][23][24][25][26] Therefore, a range of adherence rates from 30% to 100% were also applied in the model to accommodate the potential variability in real-world adherence. Higher LYG with mt-sDNA was observed compared with the blood-based test (with 10% adenoma sensitivity) at all levels of adherence, even when assuming adherence as low as 30% for mt-sDNA and as high as 100% for the blood-based test.…”
Section: Discussionmentioning
confidence: 99%